(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Women are more prone for developing thyroid dysfunction. And most common clinical presentations seen are irregular menstruation, weight gain, etc. So, there is a need for formulating a treatment protocol for the same. Aims: The present study is aimed to evaluate the effectiveness of Panchakarma along with internal medications in the management of hypomenorrhoea associated with thyroid dysfunction. Materials and methods: A female aged 38 years who was suffering from hypomenorrhoea in the last one year, associated with weight gain, and known case of hypothyroidism in the past 2 years, was enrolled for the study. She underwent Panchakarma therapy followed by internal medications for 3 months. And was followed up after the course of treatment. Results: There was significant relief in her symptoms and thyroid profile also came to normal. Conclusion: Ayurvedic management with Panchakarma therapy followed by internal medicine is having significant role in reversing the symptoms.